The Influence of the PBL Model on Temperature and Expansion Topics on Student Learning Outcomes - Assagaf, Halisa; Mursalin, Mursalin; Abdjul, Tirtawaty; Ntobuo, Nova Elysia; Buhungo, Trisnawaty Junus; Payu, Citron S. (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The Problem-Based Learning (PBL) model is a student-centered learning strategy that requires students to be skilled and sensitive in solving problems in the surrounding environment. This research aims to determine the effect of the PBL model on temperature and expansion topics on student learning outcomes. This research is experimental research, with the research design being One Group Pre-test and Post-test Design. The population of this research was class VII students of SMP Negeri 11 Gorontalo. The sample consists of 3 classes: experimental class, replication 1, and replication class 2. The data collection instruments used are validation sheets, observation sheets, and pre-test and post-test question sheets to see student learning outcomes; then, the data is analyzed using descriptive statistics and statistics. Inferential, which includes normality testing, hypothesis testing, and n-gain analysis. The results of the research show that the results of the hypothesis test are that for the experimental class, the t-count is 7.513 greater than t-table 1.697; for replication class 1, t-count 4.679 is more significant than t-table 1.720, and for replication class 2, t-count 2.080 is more important than t-table 1.729. It can be concluded that the hypothesis testing in each class is t-count greater than t-table; this can be interpreted as the influence of the PBL model on temperature and expansion topics on student learning outcomes.